101 dalmatians [videorecording (DVD)] - Geronimi, Clyde; Luske, Hamilton S.; Reitherman, Wolfgang, 1909-1985; Smith, Dodie, 1896-1990 (Disney DVD., 2008)
Pongo and Perdita have a litter of 15 dalmatian puppies. Cruella De Vil takes a fancy to the puppies and tries to buy them from their human owners, Roger and Anita. Cruella wants to get ahold of those puppies, as well as more puppies, to make herself a lovely dalmatian skin coat. Cruella hires some thugs to kidnap the puppies and hold them at an abandoned mansion. Now Pongo and Perdita must use an animal communication system to help find all the puppies.